Teachers’ knowledge of subject matter in formal definition of limit at senior high school level - Ma'rufi Ma'rufi; Muhammad Ilyas; Salwah Salwah; Nur Wahidin Ashari (CV. FOUNDAE, 2025)
Background: Vocational schools in border areas face systemic challenges such as limited infrastructure and poor curriculum-context alignment, hindering effective mathematics instruction and student engagement.Aims: This study investigates how mathematics learning is organized and implemented in a vocational high school situated in the Entikong border area of West Borneo, Indonesia. The research seeks to identify instructional patterns, contextual challenges, and adaptive strategies used by educators under constrained conditions.Method: Using a qualitative case study design, data were gathered through direct classroom observation, semi-structured interviews with teachers and school leaders, and review of official teaching documents. Thematic analysis and data triangulation were employed to ensure rigor and credibility.Results: The analysis highlights a continued reliance on teacher-centered instruction, minimal use of contextual or vocationally integrated methods, and limited student engagement. Assessment practices predominantly measure cognitive outcomes, lacking elements that support student reflection or vocational competencies. Curriculum delivery is often disrupted by time limitations and infrastructural shortfalls.Conclusion: Improving mathematics instruction in border-based vocational schools necessitates flexible teaching models tailored to the local context. Strengthening professional development, embedding authentic assessments, and enhancing school-community collaboration are crucial steps toward addressing educational disparities in underserved regions.